Strategi Guru Pendidikan Agama Islam Dalam Menanggulangi Narkoba Sebagai Upaya Meningkatkan Moral Siswa - Marzuqi, Mubarak (Impressive: Journal of Education, 2024)
The purpose of preparing this work is for Islamic Education teachers' strategies in dealing with drugs as an effort to improve student morale. This research uses the library research method by collecting and analyzing data from various literature such as books, scientific journals, research reports, seminar articles and relevant official documents. Data collection techniques involve literature searches in libraries, online databases, and academic repositories, as well as literature review and document analysis to understand the strategies of Islamic Religious Education teachers. Data analysis includes identification of main themes, categorization of data, and synthesis of information to draw conclusions and provide recommendations for implementation in educational contexts. This research reveals the strategies of Islamic Education teachers in tackling drug abuse and improving student morale through a personal approach, integrative learning and religious extracurricular activities. Routine education about the dangers of drugs is carried out in collaboration with the police, and Islamic Education teachers act as role models with consistent behavior that is imitated by students. Strengthening character through interactive curriculum, collaboration with parents, application of positive discipline, and use of technological media are also emphasized. Routine evaluation and monitoring is carried out to assess effectiveness and adjust the strategies implemented.